2016
DOI: 10.1007/s10916-016-0440-6
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Neural Network-Based Audience Response Technology in a Human Anatomy Course for Pharmacy Students

Abstract: Objective: This paper presents an empirical study of a formative neural network-based assessment approach by using mobile technology to provide pharmacy students with intelligent diagnostic feedback.Method: An unsupervised learning algorithm was integrated with an audience response system called SIDRA in order to generate states that collect some commonality in responses to questions and add diagnostic feedback for guided learning. A total of 89 pharmacy students enrolled on a Human Anatomy course were taught … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…As concludes Sancho et al (2006), the development of competencies can be achieved through the combination of different learning scenarios. Fernández-Alemán et al (2016) argues that about 87% of US pharmacy colleges use such tools as an active form of complementary learning.…”
Section: Scopusmentioning
confidence: 99%
“…As concludes Sancho et al (2006), the development of competencies can be achieved through the combination of different learning scenarios. Fernández-Alemán et al (2016) argues that about 87% of US pharmacy colleges use such tools as an active form of complementary learning.…”
Section: Scopusmentioning
confidence: 99%
“…The ARS can also improve some aspects of learning, especially those related to the resolution of quizzes, fast problem‐solving, and individual analysis of student's progress (Alexander et al, 2009; Hoyt et al, 2010; Fernández‐Alemán et al, 2016). In addition, when used in a smartphone application (Chung et al, 2018), this technology becomes very accessible and becomes a good possibility for the anatomy teacher to choose.…”
Section: Discussionmentioning
confidence: 99%
“…In 10 (3%) of the studies included in the research, they compared the traditional learning method and mobile application methods to investigate the effect of mobile learning. In 8 (26%) of the studies, it was observed that the final exam results of the students who learned anatomy with the mobile application were higher than the students who learned with the traditional method (Chakraborty & Cooperstein, 2018;Fernández-Alemán, López-González, et al, 2016;Fernández-Alemán, Lopez-Gonzalez, et al, 2016;Lazarus et al, 2017;Moro et al, 2017;Traser et al, 2015;Wilkinson & Barter, 2016;Wilkinson et al, 2020). In the other 2 (6%) studies, it was observed that the anatomy final exam results of the experimental groups were higher, but there was a decrease in their cognitive levels (Bork et al, 2021;Küçük et al, 2016).…”
Section: Surveymentioning
confidence: 99%
“…Within the scope of the systematic review, it was stated in 20 (66%) studies that mobile learning facilitates three-dimensional learning, is motivating and fun. They stated that they can access anatomy notes and images at any time of the day (Bolatli & Kizil, 2022;Bork et al, 2021;Fernández-Alemán, López-González, et al, 2016;Gnanasegaram, Leung, & Beyea, 2020;Golenhofen et al, 2020;Havens, Saulovich, & Saric, 2020;Jamali, Shiratuddin, Wong, Oskam, & Sciences, 2015;Kurniawan & Witjaksono, 2018;Küçük, Kapakin, & Göktaş, 2016;Lazarus, Sookrajh, & Satyapal, 2017;Mendez-Lopez et al, 2022;Mogali et al, 2019;Moro, Štromberga, Raikos, & Stirling, 2017;Morris, Lambe, Ciccone, & Swinnerton, 2016;Pickering, 2015;Stewart & Choudhury, 2015;Stirling & Birt, 2014;Traser, Hoffman, Seifert, & Wilson, 2015;Wilkinson & Barter, 2016;Wilkinson et al, 2020). In 19 (63%) studies, the learning effectiveness of medical school students in anatomy education with mobile applications was investigated, and positive feedback was received from the students.…”
Section: The Effect Of Anatomy Learning With a Mobile Application On ...mentioning
confidence: 99%